Functional characterization of poplar and Arabidopsis wood - related hydrolases by reverse genetics and overexpression in Arabidopsis - Olive, Emmanuel (2006)
Trees and their wood present a very valuable and renewable resource (paper industry, raw materials and constructions). Consequently study of wood formation is an important research field. The wood or secondary xylem is formed from the vascular cambium where meristematic activity takes place. During differentiation of wood cells, there is radial expansion and intrusive tip growth phase followed by the secondary wall deposition and programmed cell death. Cell expansion and intrusive tip growth is regulated by the plasticity of the primary cell wall. This wall is composed of pectin, cellulose, hemicelluloses (xyloglucans in particular), and proteins including some wall residing enzymes that are important for regulating wall plasticity. To study the process of wood cell expansion, I focused on a two kinds of hydrolases expected to be involved in the cell wall plasticity/biosynthesis: xyloglucan endotransglycosylases and cellulases. Xyloglucan endotransglycosylases /hydrolases (XTHs or formerly XETs) are enzymes capable of mediating the endocleavage of a xyloglucan molecule and the re-ligation of the cut donor to the acceptor that is another xyloglucan molecule or, in some cases, the water. Cellulases on the other hand are ≤,1-4 endoglucanases and could hydrolyze cellulose or hemicellulose molecules. Both these enzymes exist as multigene families and it is a challenge to determine the function of individual members of these families.